Les « portraits de portrait » de Jim Campbell : ambiguïté et traitement de l’information - Masse, Isabelle (RACAR : Revue d'art canadienne / Canadian Art Review, 2014)
The ability or inability to perceive facial features and expressions has a direct impact on communication. In this sense, the clarity or elusiveness of the image in the experience of portraiture should influence spectatorship. It is from this perspective that American artist Jim Campbell uses scientific references to explore the effects of visual ambiguity in electronic portraits belonging to his series “Ambiguous Icons.” This article focuses on two of these portraits, namely a matching pair in which the medium significantly obfuscates the representation: Portrait of a Portrait of Harry Nyquist and Portrait of a Portrait of Claude Shannon (2000). The sitters are two scientists whose work laid the foundation for information theory, a mathematical model of communication originally created for telecommunications, but whose applications later extended to cognitive science. I examine how these artworks, by material and formal means, can be understood as artistic analogies of information theory and then argue that through this theoretical reference they evoke a traditional model of human cognition. Lastly, I discuss the strategies adopted to elicit the viewer’s response from two perspectives: the perceptual experience and, more broadly, the aesthetic experience, respectively analyzed through the artist’s reinterpretation of a 1973 experiment on facial recognition and through a 1960s transposition of information theory to the arts.